Examination of Far-Field Mathematical Absorber Reflection Suppression through Computational Electromagnetic Simulation - S. F. Gregson; A. C. Newell; G. E. Hindman (International Journal of Antennas and Propagation)
The mathematical absorber reflection suppression (MARS) technique has been used to identify and then suppress the effects of spurious scattering within spherical, cylindrical, and planar near-field antenna measurement systems, compact antenna test ranges (CATRs), and far-field measurement facilities for some time now. The recent development of a general-purpose three-dimensional computational electromagnetic model of a spherical antenna test system has enabled the MARS measurement and postprocessing technique to be further investigated. This paper provides an overview of the far-field MARS technique and presents an introduction to the computational electromagnetic range model. Preliminary results of computational electromagnetic range simulations that replicate typical MARS measurement configurations are presented and discussed which, for the first time, confirm through simulation many of the observations that have previously been noted using purely empirical techniques.